Awareness and Perception Regarding Human Milk Donation and Milk Banking among Antenatal Mothers in a Tertiary Hospital of Kathmandu – A Cross - sectional Study - Dhakal Chalise, Gita; Ale, Pabitra; Budhathoki, Babita; Bharati, Mamata (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Breast milk is universally recognized as the most beneficial source of nutrition for all newborns. World Health Organization (WHO) recommends the use of donor human milk to sick and normal newborns if mother’s milk is unavailable to them. The objective of this study was to assess the awareness and perception regarding human milk donation and human milk banking among antenatal mothers. Methods: A descriptive cross-sectional study was carried out among 165 antenatal mothers. Data were collected via face-to-face interviews after obtaining informed written consent. Descriptive and inferential statistics were used to analyze the findings. Results: From the study findings, 43.6% antenatal mothers had average awareness level whereas 38.8% had adequate, and 17.6% had an inadequate awareness level. Similarly, 66.7% antenatal mothers had positive perception and 33.3% had negative perception regarding this. The level of awareness and perception was significantly associated with age (P = 0.001), educational status (P = 0.002), residence (P = 0.013) and religion (P = 0.004). Conclusions: Antenatal mothers tend to have average awareness and positive perception regarding human milk donation and milk banking. As there is positive perceptions of human milk donation and milk banking among them, this practice should be promoted to improve the nutritional benefit for infant and non-nutritional benefit for mother.